2004
DOI: 10.1191/1352458504ms1008oa
|View full text |Cite
|
Sign up to set email alerts
|

Caregivers of people with multiple sclerosis: experiences of support

Abstract: The aim of this phenomenological study was to gain an understanding of the experiences of a group of caregivers of people with multiple sclerosis (MS). Sixteen caregivers from Northern Ireland and the Republic of Ireland participated in focus group interviews. The theme of support, either sought or received, emerged as a major aspect of the experiences described. Caregivers' feelings about, and experiences of, support appeared to change over time. Four common phases that caregivers experienced in relation to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
68
0
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(72 citation statements)
references
References 37 publications
0
68
0
4
Order By: Relevance
“…Moreover, there are no known studies about this field in MS patients. However, some studies have shown that participation in supporting groups for patients with MS was strongly linked to decreased anxiety and increased satisfaction with life 21 , and supporting a person with MS had an impact on the lives of informal caregivers 28 . One explanation for the low frequency of this type of analysis may be linked to the fact that the concept of a SSN is poorly defined, due to the heterogeneity in the analysis of its dimensions held by investigators, and it sometimes is confused with other close concepts, such as social support 17,29 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there are no known studies about this field in MS patients. However, some studies have shown that participation in supporting groups for patients with MS was strongly linked to decreased anxiety and increased satisfaction with life 21 , and supporting a person with MS had an impact on the lives of informal caregivers 28 . One explanation for the low frequency of this type of analysis may be linked to the fact that the concept of a SSN is poorly defined, due to the heterogeneity in the analysis of its dimensions held by investigators, and it sometimes is confused with other close concepts, such as social support 17,29 .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, McKeown, Porter-Armstrong, and Baxter (2004;Article #5) found that most carers were unable to request family members' or friends' support because they were unable to share their problems and thought it was unfair to ask for their support. In contrast, some carers reported that their families or friends did not want to get involved, therefore they chose not to offer …”
Section: External Stressorsmentioning
confidence: 99%
“…Article #2). For instance, McKeown et al (2004;Article #5) reported that although some early-and middle-stage carers were resisting asking for support from their families and unwilling to receive help from them, they reported that they were disappointed and upset that their families did not offer their support or that they stopped offering as the time passed and the disease progressed.…”
Section: Experiences Of Supportmentioning
confidence: 99%
“…As the disease progresses the sufferer may encounter physical impairments including muscle weakness and compromised use of limbs, dizziness and pain as well as cognitive deficits such as short term memory loss 1 .The disease is characterised by periods of relapse and remission with some people going on to develop secondary progressive MS where symptoms gradually worsen and there are fewer or no periods of remission 2 . MS patients face considerable challenges in terms of adjusting to and coping with the disease 3 , but the act of caring for someone with MS brings its own challenges, with carers reporting a wide range of problems, including negative effects on their physical, social, and psychological well-being (see review 4 ). This is a significant issue, given both the scale and psychological consequences reported.…”
Section: Introductionmentioning
confidence: 99%